Spatial data analysis : theory and practice - Haining, Robert P. (Cambridge University Press, 2003)
Spatial data are data about the world where both the attribute of interest, and its location on the earth are recorded. Are there geographic clusters of disease cases, or hotspots of crime, for example? This comprehensive overview explains all for students and researchers in geography, social science and environmental science.